Expression of Absorptive Capacity in a Regional Innovation System of Lithuania: an Approach to Sampling for Qualitative Research - Juknevičienė, Vita (Socialiniai tyrimai, 2016)
Absorptive capacity is the one of key phenomena, explored by researchers interested in innovation management. Each regional innovation system consists of a variety of interlinked actors – institutions characterized by various specifics. The article presents a qualitative approach to the expression of absorptive capacity in a regional innovation system and identifies the main sampling challenges. Valid and credible results of representative sampling for qualitative research on the expression of absorptive capacity in a regional innovation system of Lithuania should follow a five-step process. It ensures multidimensional approach to the specificity of the analyzed object as well as its context. The article provides evidence on how this process has been adjusted for this particular empirical research in Lithuania.
Keywords: regional innovation system; absorptive capacity; sampling